A Fully Functional Enterprise Resource Planning (ERP) System for Honey Home Company in Indonesia - Mohammed Saleh Mohammed Ba Karman; Cahyo Darujati; Ani Wulandari (NAROTAMA UNIVERSITY, 2022)
Honey Home Company specializes in providing high-quality honey; however, the company is experiencing numerous difficulties in monitoring the business changes; thus, implementing an ERP system might adjust these issues. This study aims to identify the ERP system's requirements to fulfill the company's needs, design and implement the system, and highlight the benefits of implementing the system in the business. A qualitative method of interviewing the system's users and providing a survey questionnaire was utilized to analyze the impacts of implementing an ERP System on the business. The findings indicate that Honey Home Company benefited from the ERP System regarding time savings, information quality, service quality, user satisfaction, and staff performance.